Applying Google earth engine for flood mapping and monitoring in the downstream provinces of Mekong river - Bui Phan Quoc Nghia; Indrajit Pal; Nuwong Chollacoop; Anirban Mukhopadhyay (Progress in Disaster Science, 2022)
Flood is a hazard, but it is also essential for the local communities in the Mekong Delta, as it also provides nutrients for agriculture and resists saltwater intrusion. In recent years, changes in flood patterns have been observed in the Mekong Delta with erratic fluctuations in the flooded area, especially in the downstream provinces. It causes a lot of difficulties in flood monitoring and management in this area. Therefore, a robust assessment of flood shifting is essential in the Mekong Delta. This work addresses the development of a logical model based on Google Earth Engine (GEE) using Sentinel-1 synthetic aperture radar (SAR) data to assess floods in the downstream Mekong River basin. In the present study, the observed data of Tan Chau and Chau Doc hydrological stations have been used to test and prove the reliability of this application. The inundation scenario generated from this study showed a gradual shift in flooding patterns of the downstream provinces of the Mekong Delta. Overall, the flooded area is decreasing; however, the same is increasing in Bac Lieu province. This research will help to construct a professional support system to monitor the flood inundation in the Mekong Delta. They can give local authorities a big picture of inundation to decide on flood disaster preparedness, mitigation, and adaptation.